INTERNET COUNSELING PASTORAL RELATIONSHIP FOLLOWER EARLY DETECTION DATA PROCESS (ICPRF) - Maryo Indra Manjaruni (Green Publisher, 2023)
The church, as a spiritual and social institution, plays an important role in the life of society. In it, various service processes are carried out to fulfill the spiritual and social needs of the congregation. In an effort to improve the effectiveness and efficiency of church services, an in-depth understanding of the performance of ministry processes becomes very important. That is why Process Mining, a revolutionary approach in data analysis, comes as an invaluable tool to help uncover potential improvements in church ministry. Early detection is the process or effort to identify a problem, disease, risk, or event early, usually before more serious symptoms or impacts arise. The main goal of early detection is to take appropriate action as quickly as possible, so that the problem can be addressed or managed more effectively, and its negative impact can be minimized.